Meta-Analysis of the Effect of Using Integrated Student Worksheets Innovative Natural Science Learning Models to Improve High Order Thinking Skills of High School Students - Hilmi Rizki Anjani; Nadya Syahdi; Utari Prisma Dewi; Festiyed; Asrizal (Jurnal Penelitian Pendidikan IPA, 2023)
Many studies have been conducted on the effect of student worksheets on student High Order Thinking Skills abilities. However, this research is still limited to aspects of research variables, especially moderator variables. The solution to this problem is to do a meta-analysis of the effect of worksheets on student High Order Thinking Skills abilities. The research objective was to determine the effect of worksheets on student High Order Thinking Skills abilities based on class levels, subjects, and learning models. The method used in this study is the method of meta-analysis, examining several articles in national and international journals. Â The number of samples taken used 25 articles related to scicence worksheets with 11 Physics articles, 7 Biology articles, 7 Chemistry articles. Articles reviewed from 2018-2022. The results of the analysis show that the use of worksheets has a significant effect on student High Order Thinking Skills abilities both in terms of class level, subjects, and learning model. Thus, the use of worksheets is effective for increasing student High Order Thinking Skills abilities at various grade levels, subjects, and learning models. Based on the research results using worksheets in physics learning is a good solution to improve student High Order Thinking Skills abilities.